Saturday

August 2, 2014

August 2, 2014

Posted by **Chely** on Thursday, March 14, 2013 at 11:51pm.

----------- • ------------ = ?

3a2-6a-3 9ab

- Math -
**Steve**, Friday, March 15, 2013 at 10:00am3a^2-6a-3 = 3(a-1)^2, so we end up with

27a^4b^7(a-1) / 27ab = a^3b^6/(a-1)

**Related Questions**

math - 3a2-9ab+4b2-7ab=

math - 3a2 - (3a - x + b)

math - be found arithmetic series 3a2-a6=-a2 a3+a4=19

math - I need help solving this subtraction (xy-ab-3)- (xy-9ab-1) the answe is ...

math - DETER MINE THE PRODUCT OF THE FOLLOWING.1.(3Y+4X)(3Y-4X) 2.(p1/2Q)2 3.(A+...

math - DETER MINE THE PRODUCT OF THE FOLLOWING.1.(3Y+4X)(3Y-4X) 2.(p1/2Q)2 3.(A+...

math - sums and differences of rational algebraic expression please answer the ...

Math - Find the HCF 1) 7x and 9 : nothing 2) x^2(x-4) and x(x-4) : its (x-4)? 3...

8th grade - If f(x)=4x-5 find the value. f(c) f(3a2)

math - 1)Which values of x are in the solution set y=3x-1 y=x^2-5x+6 2)6ab (...